الكلمات الشائعة في المدونات النصية الأكاديمية الخاصة بالنصوص العربية في الجامعة الإسلامية العالمية بماليزيا: برنامج المنقب العربي نموذجا - Masitah binti Abd Aziz (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2015)
The purpose of the current study is to identify common Arabic words in the academic field through Arabic Corpus. These words are available in the “Arabic Concordancer”. Based on the research objectives, this research reviewed numerous numbers past research on Corpus (Arabic and non-Arabic) to discover the existing corpus after the revision of the three divisions of Arabic word groups: nouns, verbs, and connectives to distinguish between these common words in order to analyse the available data. The significance of this research is to assist students to use common words in the correct phrases in the academic fields: Arabic Language Studies and Islamic Studies through the observation of the selected words contained in the corpus. This study was conducted by using descriptive computational analytical methodology to suit the nature of the research which requires computational analysis to analyse the common words as well as to indicate the specific linguistic characteristics. The results show that the highest frequency of words used are the connectives compared to nouns and verbs. The frequency of repeated word in the first one hundred words are connectives with 572,941 followed by nouns 397,264 and verbs 38,451. These were categoried based on the specific characteristic in the linguistic area. Research also found that there are some ambiguous words due to the lack of harakat (phonetic aid) and tagging used in this corpus. These words are (إذ، إذا، إن، أن، أي، بين، حول، دون، عبد، علم، غير، قبل، لم، ما، من). This study elaborates the ambiguities that exist in these words so that it may benefit learners in understanding them better.